Identificación de una aspartato proteasa producida por Amylomyces rouxii, silenciamiento del gen que la codifica y efecto sobre la actividad tirosinasa - Marcial Quino, Jaime (Universidad Autónoma Metropolitana, 2011)
Amylomyces rouxii is a zigomycete, it was isolated from a paper industry effluent and has studied for pentachlorophenol (PCF) degradation, it has been reported that A. rouxii produces an extracellular phenoloxidase (tyrosinase) involved in the toxic degradation. This strain was used in the biochemistry and molecular studies of this work. In this work, it was showed that A. rouxii produces extra and intracellular phenoloxidases, type tyrosinase. An extracellular phenoloxidase produced by A. rouxii was partially purified and the partially purified enzyme showed activity on different phenolic substrates (mono and diphenol). However, the amino terminal sequence of the protein obtained do not showed similitude with the phenoloxidase, in spite it was found similitude with an aspartate protease, indicating that probably the interest protein was contaminated with a protease or it was selectivity purified a protease. It was observed that under culture conditions used, A. rouxii produces an extracellular protease at the same time that the tyrosinase is produced (48 h). This secreted protease was purified by anionic interchange chromatography, it was obtained a purification factor of 4.2 and a similar molecular mass to the phenoloxidase (40 kDa) determined by SDS-PAGE. The sequence was obtained by LC-MS/MS and the analysis of sequence revealed that this protein correspond to an aspartate protease type 2, also named rhizopuspepsin-2, with 99% of similitude to a rhizopuspepsin-2 from Rhizopus oryzae. Optimum pH of this purified enzyme was 3.5, using hemoglobin as substrate and was stable between 37 to 50° C. In presence of protease inhibiter pepstatin A at 3mM, protease activity diminished 3.6-time, while tyrosinase activity increased 2-time with respect to assays without inhibiter. For this reason we proposed study the effect of this protease on tyrosinase activity, through diminished protease activity by silencing of the protease gen of A. rouxii, using a RNA interference mechanism. The fragments of rhizopuspepsin-2 of 412 and 910 pb were obtained from the gen that codify it from the purified protease of A. rouxii. While, the fragment of rhizopuspepsin-6 of 455 pb was obtained from the sequence of the gen that codify it, presented in data base GenBank of the Rhizopus oryzae. Plasmids were constructed with each one of the fragments, inserted between two promoters in sense opposite, Pgpd y Ppki. It was selected 5 transformants obtained frond A. rouxii, containing the plasmid with the x fragment of 412 pb, and 2 transformants containing the fragments of 910 and 2 of 455 pb. The transformant A412-3 presented the highest protease activity inhibition, 80 and 91 % at 48 and 96 h of culture respectively, the transformants obtained with the fragment of 910 pb inhibited 25% protease activity at 48 h. The transformants obtained with the fragment of 455 pb presented 65% of protease activity inhibition, also at 48 h. The transformants were used to study the effect of protease on tyrosinase activity. A412-3 transformant, from rhizopuspepesin-2, showed 4-times higher monophenolase activity using L-tyrosine as substrate, and 2.7-times and 2-times higher diphenolase activity using L-dopa and 4-ter-butylcatecol as substrates respectively, all these results compared with tyrosinase activity of the wild strain of A. rouxii. However, transformants obtained from the fragment of rhizopupspepsin-6 do not produce higher tyrosinase activity. Results indicate that the tyrosinase produced by A. rouxii is negatively affected by the aspartate protease type 2, and probably the aspartate protease type 6 does not affect tyrosinase activity. Phenoloxidase produced by transformant A412-3 of A. rouxii was partial purified. Enzyme purification was carried out by anion interchange and by gel filtration chromatography, the final purification factor was 8.2 to monophenolase activity and 10.6 to diphenolase activity. The two bands obtained from an acrylamide gel showed a molecular mass of 43 and 128 kDa, these bands were sequenced by mass spectrophotometry. The bands showed 100% similitude to a tyrosinase and poliphenoloxidase from Agaricus bisporus, while for Pholia nameko (38%), Lentinula edodes (37%), Pycnoporus sanguineus (33%) and Neurospora crassa (27%). Finally, we identified the protein produce by A. rouxii as an extracellular tyrosinase. Results suggest that the aspartate protease type 2 produced by A. rouxii, identified in this work could de involved in a post-transductional regulation mechanism in the tyrosinase of A. rouxii.; Amylomyces rouxii es un zigomiceto, aislado de un efluente de la industria de papel y que ha sido estudiado para la degradación de pentaclorofenol (PCF), encontrándose que produce una fenoloxidasa (tirosinasa) extracelular involucrada en la degradación del tóxico. Cepa que se empleó en todos los estudios bioquímicos y moleculares mencionados en este documento. En el presente trabajo se mostró que A. rouxii produce fenoloxidasas extra e intracelulares, de tipo tirosinasa. Se purificó parcialmente una fenoloxidasa extracelular producida por A. rouxii y la enzima semipurificada mostró actividad con diferentes sustratos fenólicos (mono y difenoles). Sin embargo, la secuencia del amino terminal de la proteína no se encontró la fenoloxidasa sino que dicha secuencia presentó similitud con una aspartato proteasa, lo que indicaba que probablemente la proteína de interés estaba contaminada con una proteasa, o bien que se estaba purificando selectivamente una proteasa. Se observó que, en las condiciones de cultivo utilizadas, A. rouxii produce proteasa extracelular, en los mismos tiempos en los que se produce la tirosinasa (48 horas). La proteasa secretada fue purificada por cromatografía de intercambio aniónico, obteniéndose un factor de purificación de 4.2 y una masa molecular similar a la de la fenoloxidasa (40 kDa), determinada por SDS-PAGE. La secuenciada fue obtenida por LC-MS/MS y su análisis reveló que corresponde a una aspartato proteasa tipo 2 (también llamada rhizopuspepsina-2), con 99% de similitud a la de Rhizopus oryzae. El pH óptimo de la rhizopuspepsina purificada fue de 3.5, utilizando como sustrato hemoglobina y fue estable en un rango de temperatura de 37 a 50ºC. En presencia del inhibidor de proteasas pepstatina A, 3 mM, la actividad proteasa disminuyó 3.6 veces, mientras que la actividad tirosinasa se incrementó 2 veces con respecto a los cultivos sin inhibidor. Por esta razón, se propuso estudiar el efecto de esta proteasa sobre la actividad tirosinasa, a través de la disminución y/o eliminación de su actividad en A. rouxii, mediante el silenciamiento de su gen, mediado por un mecanismo de RNA de interferencia. Los fragmentos de 910 y 412 pb de la rhizopuspesina-2 se obtuvieron a partir del gen codificante de la proteasa purificada de A. rouxii. Mientras que el fragmento de 455 pb del gen de la rhizopuspepsina-6, se obtuvo de la base de datos GenBank a partir de la vii secuencia del gen que codifica para esta enzima, del hongo Rhizopus oryzae. Se construyó un plásmido con cada uno de los fragmentos de genes de rhizopuspepsina, insertado entre dos promotores orientados en sentido contrario, el Pgpd y Ppki. Se seleccionaron 5 transformantes, provenientes de A. rouxii, con la construcción que incorporaba el fragmento de 412 pb y 2 con con cada uno de los fragmentos de 910 y 455 pb. La transformante A412-3 presentó mayor inhibición de actividad proteasa, 80%, y 91% a las 48 y 96 h de cultivo, respectivamente, mientras que las transformantes obtenidas con el fragmento de 910 pb inhibieron el 25% de la actividad proteasa a las 48 h. Las dos transformantes obtenidas con el fragmento de 455 pb presentaron 68% de inhibición de la actividad proteasa a las 48 h de cultivo. Las transformantes seleccionadas se usaron para estudiar su efecto sobre la actividad tirosinasa. La transformante A412-3, con un fragmento de la rhizopuspepsina-2, incrementó, a las 48 h de cultivo, 4 veces la actividad monofenolasa utilizando L-tirosina como sustrato e incrementó 2.7 y 2.0 veces la actividad difenolasa con L-dopa y 4-tertbutilcatecol como sustratos, respectivamente. Sin embargo este efecto no se observó en las transformantes con el fragmento de la rhizopuspepsina-6, ya que no se obtuvo incremento de actividad tirosina en los sustratos analizados. Los resultados obtenidos permiten proponer que la fenoloxidasa producida por A. rouxii es afectada de manera negativa por la aspartato proteasa de tipo 2, lo que provoca una disminución de su actividad y la posible degradación de la proteína, mientras que la proteasa de tipo 6 probablemente no afecta a la fenoloxidasa. A partir de la transformate A412-3, se volvió a purificar parcialmente la fenoloxidasa. La purificación se realizó mediante cromatografía de intercambio aniónico y filtración en gel, obteniéndose un factor de purificación final de 8.2 para la actividad monofenolasa y 10.6 para la actividad difenolasa. Las dos bandas obtenidas a partir de la cromatografía por filtración en gel, visualizadas en geles de acrilamida con un tamaño de 43 y 128 kDa, fueron secuenciadas por espectrometría de masas. Las bandas mostraron 100% de similitud a una tirosinasa y polifenoloxidasa de Agaricus bisporus, mientras que solo el 38%, 37%, 33% y 27% de similitud con tirosinasas de especies como Pholiota nameko, Lentinula edodes, Pycnoporus sanguineus y Neurospora crassa, respectivamente. Finalmente, identificamos la proteína producida por A. rouxii como una tirosinasa viii extracelular. Los resultados sugieren que la aspartato proteasa de tipo 2 identificada podría estar involucrada en un mecanismo de regulación post-transduccional de la tirosinasa de A. rouxii.